Cluster dynamical mean-field study of intra-unit-cell charge nematicity in hole-doped cuprates - Abhishek Kumar; David Sénéchal; A.-M. S. Tremblay (Proceedings of the National Academy of Sciences, 2025)
Recent scanning-tunneling microscopy on hole-doped Bi 2 Sr 2 CaCu 2 O 8 , one of the materials of the cuprate family, finds a long-range ordered spontaneous splitting of the energy levels of oxygen orbitals inside the CuO 2 unit cells [S. Wang et al ., Nat. Mat. 23, 492–498 (2024)]. This spontaneous intra-unit-cell orbital ordering, also known as electronic nematicity, breaks C 4 symmetry and is thought to arise from the Coulomb interaction (denoted by V pp ) between oxygen p x and p y electrons. In this work, we study the spontaneous emergence of electronic nematicity within the three-band Hubbard [aka the Emery-VSA (Varma-Schmitt-Rink-Abrahams) model], using cluster dynamical mean-field theory. This method incorporates short-range electronic correlations and gives us access to the density of states, a quantity that is directly probed in experiments. We argue that there is a delicate competition between V pp and V pd (the latter being the Coulomb interaction between copper d x 2 − y 2 and oxygen p x , y electrons) that must be taken into account in order to find a Zhang-Rice singlet band well-resolved from the upper Hubbard band, and a splitting of the charge-transfer band (one of the signatures of charge nematicity) by roughly 50 meV, as observed recently.